Pemberdayaan Kader Kesehatan: Meditasi Mindfulness dan Yoga sebagai Manajemen Hipertensi - Febrina Secsaria Handini; Oda Debora (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Hypertension is one of the diseases that can be prevented, but it is necessary to have management that can improve the quality of life and prevent complications due to hypertension. Hypertension management can use pharmacological and non-pharmacological methods. Non-pharmacological management can use yoga and mindfulness meditation as complementary therapies. Objective: To improve the knowledge of health cadres about hypertension management and to improve knowledge and skills of complementary therapies that can be used to help control hypertension through mindfulness meditation and yoga. Method: During the session, we used discussions and direct practice method. Result: The participation of cadres in this activity is 67% of the total expected target, this is because cadres have other activities that cannot be abandoned. In addition, from this activity, there is an increase in the knowledge of cadres about hypertension and an increase in skills and capabilities in practicing mindfulness meditation and yoga. Conclusions: Some research results on the practice of mindfulness meditation and yoga regularly can help control blood pressure in people with hypertension. Meditation and yoga exercises can be carried out regularly in order to provide optimal impact. We recommend that you still carry out yoga exercises accompanied by experienced instructors to prevent physical injury due to movement errors, especially if you have never done yoga. Regular exercise is expected to help control hypertension.